THE IMPORTANCE OF THE ABA METHOD FOR THE PROFESSIONAL PRACTICE OF THE PSYCHOPEDAGOGUE - Claudia Lima dos Santos Agapito, Débora; Agapito dos Santos, David (Revista Gênero e Interdisciplinaridade, 2025)
This work, "The Importance of the ABA Method for the Professional Practice of the Psychopedagogue," is the result of a research project developed during the Scientific Work Methodology course. This original article was constructed within the scope of a bibliographic study, whose object of investigation was the close relationship between the professional practice of the Psychopedagogue and the use of the ABA Method in psychopedagogical offices for the care of learners, both autistic and non-autistic. Psychopedagogy is a human science that today is strictly focused on the learning difficulties of individuals at any age and/or school stage, seeking to improve their learning acquisition through the adoption of methods that enable this process, adding quality to the service provided. The research stemmed from a curiosity sparked during the studies of the ABA Method course at the Faculty of Sciences of Bahia, during which we realized that the ABA Method, through its main theoretical framework based on Watson's behaviorist theory, can be a good method to be used in other cases, not only with autistic individuals. This is a bibliographical research study, based on interviews and observations of several psychopedagogical sessions using the ABA Method with autistic and non-autistic learners, to discuss the importance of this method for the daily professional practice of the Psychopedagogue.